Safety Performance Assessment of Hazardous Chemical Facilities in Bangladesh Using Indexing Approach (Chemical Engineering Research Bulletin, 2021)
This paper presents evaluation of safety performance of three hazardous facilities based on current safety practice by measuring their safety weighted hazard indices (SWeHI) of multifarious units of chemical process and what can be done to avoid any potential accidents in context of Bangladesh. Assessing hazard potential over safety procuration is a key indicator of how well a facility is prepared to reduce its vulnerability. The risks associated with hazardous facilities are always greater in a country like Bangladesh as the safety issues are not often been prioritized by its key stakeholders. In recent years, there were number of deadly accidents occurred in the chemical industries and storage warehouses which resulted multiple fatalities and significant property damage. The accident could be avoided using proper safety protocols in those facilities. Here safety performance of three facilities was assessed based on survey data. These facilities deal with flammable, explosive and toxic chemicals. This index is on the basis of fire & explosions properties and toxic release properties as well as the safety precautions against it. It helps professionals to identify the overall hazard potential and distinguish less protected units from other well operated units. The paper features on an approximate yet workable assessment of risks at a low cost and based on the current safety practices.Chemical Engineering Research Bulletin 21(2020) 60-68